Pengaruh Disiplin Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Dikantor Kecamatan XX - Maimunah; Rycha Kuwara Sari; Ferawaty Puspitorini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine or test (1) the influence of work discipline on the performance of employees at the XX District office (2) the influence of workload on the performance of employees at the XX District office (3) the influence of work discipline and workload on the performance of employees at the XX District office. This type of research is quantitative research. The population in this study were employees at the XX District office. The data analysis method uses multiple linear regression, validity and reliability testing, heteroscedasticity testing, and hypothesis testing. The data was processed using IBM SPSS version 23 software. The results showed that (1) work discipline had a positive effect on employee performance at the XX District office (2) workload had a positive effect on employee performance at the XX District office (3) work discipline and workload had a simultaneous effect on employee performance at the XX District office.